Depositional process of hyperpycnal flow deposits: A case study on Lower Cretaceous Sangyuan outcrop in the Luanping Basin, Northeast China - De-zhi Yan; Ru-kai Zhu; Hao Shou; Zhao-hui Xu; Wei-hong Liu; Si-cheng Zhu; Zhi-cheng Lei; Jing-ya Zhang; Chang Liu; Yi Cai; Huai-min Xu (China Geology)
ABSTRACT: Sedimentary process research is of great significance for understanding the distribution and characteristics of sediments. Through the detailed observation and measurement of the Sangyuan outcrop in Luanping Basin, this paper studies the depositional process of the hyperpycnal flow deposits, and divides their depositional process into three phases, namely, acceleration, erosion and deceleration. In the acceleration phase, hyperpycnal flow begins to enter the basin nearby, and then speeds up gradually. Deposits developed in the acceleration phase are reverse. In addition, the original deposits become unstable and are taken away by hyperpycnal flows under the eroding force. As a result, there are a lot of mixture of red mud pebbles outside the basin and gray mud pebbles within the basin. In the erosion phase, the reverse deposits are eroded and become thinner or even disappear. Therefore, no reverse grading characteristic is found in the proximal major channel that is closer to the source, but it is still preserved in the middle branch channel that is far from the source. After entering the deceleration phase, normally grading deposits appear and cover previous deposits. The final deposits in the basin are special. Some are reverse, and others are normal. They are superimposed with each other under the action of hyperpycnal flow. The analysis of the Sangyuan outcrop demonstrates the sedimentary process and distribution of hyperpycnites, and reasonably explain the sedimentary characteristics of hyperpycnites. It is helpful to the prediction of oil and gas exploration targets in gravity flow deposits.